Pemahaman Konsep Kimia Asam Basa Siswa Kelas XI SMAN 7 Mataram Menggunakan Instrumen FTMC - Muliana Lutfiatussholihah; Mukhtar Haris; Dodiy Firmansyah (Chemistry Education Practice, 2026)
This study aims to determine and explain the understanding of acid-base chemistry concepts among 11th grade students at SMAN 7 Mataram. The type of research used is quantitative descriptive. The study was conducted in classes XI A3 and XI B1 with a total of 69 students, or 25% of the population of 273 students. Data were collected using a four-tier multiple-choice (FTMC) test instrument consisting of 17 valid questions. The results of this study indicate that the level of understanding of acid-base chemistry concepts among 11th grade students at SMAN 7 Mataram is 57.80%, which is classified as moderate, with a distribution of concept understanding as follows: understanding the concept (39.56%), misconceptions (36.91%), and not understanding the concept (23.53%) in the low category. The level of understanding of acid-base chemistry concepts among students in grades XI A3 and XI B1 was 61.27% and 54.01%, respectively, which is classified as moderate. The highest category of concept understanding among students in class XI A3 was that quite a lot of students understood the concept (49.07%) in the material on pH calculation of solutions, quite a lot of students had misconceptions (45.83%) in the material on acid-base strength, and a few students did not understand the concept (29.17%) in the material on acid-base strength. Meanwhile, the highest category of concept understanding among students in class XI B1 was that few students understood the concept (38.64%) in the material on acid-base indicators, quite a few students had misconceptions (45.46%) in the material on pH calculation of solutions, and few students did not understand the concept (31.82%) in the material on acid-base strength.